Pengelolaan Wisata Syariah Pantai Carocok Painan Menurut Tinjauan Hukum Ekonomi Syariah - Marboro, Panji (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2023)
This study aims to describe how the implementation of Sharia Regional Regulation on the application of halal tourism at carocok beach Painan, South Coastal district. The formulation of the problem of this research is how the Sharia Regional Regulation in encouraging the application of halal tourism on the carocok beach of the South Coastal Regency and what factors are the obstacles to the application of halal tourism on the carocok beach of Painan, South Coastal Regency. This type of research is qualitative research. Data collection techniques are interviews, observation and documentation and data analysis techniques used are data reduction, data presentation and conclusion drawing/verification. The results of this research show that the implementation of the Sharia Regional Regulation in the South Pesisir district will encourage the implementation of halal tourism and sharia regulations have been implemented as much as possible by the local government, especially for tourist objects, starting from supervision, controlling the sale of liquor in the beach area and the appeal to dress Muslim / muslimah to the people of South Pesisir. Factors that hinder the application of halal tourism at Carocok Painan Beach are the absence of halal certification, lack of understanding of the South Coastal community towards halal tourism, inadequate facilities and infrastructure, no detailed rules related to halal tourism from the local government.